Endeudamiento : determinante de riesgo de quiebra (2018)
The main objective of this paper is to determine the incidence of capital structure, specifically debt levels, in the probability of an organization to declare bankrupt. In order to achieve this goal financial information was gathered from organizations of 16 countries, afterwards a Logit methodology was used.